Strategic Choice of Presentation Format: The Case of ETR Reconciliations - Chychyla, Roman; Falsetta, Diana; Ramnath, Sundaresh (The Accounting Review, 2022)
ABSTRACT To minimize costs related to unfavorable perceptions of their tax-related activities, firms with low effective tax rates (ETR) could avoid, where possible, explicit mentions of their effective tax rates. Using this reputational cost perspective, we study an item of required disclosure in the income tax footnote of the 10-K, the ETR reconciliation table, where firms can choose a presentation format that reveals the tax rate (the percentage format) or one that avoids explicit mention of the effective tax rate (the dollar format). We find that firms with low ETRs are 24 percent more likely to use the dollar format and are also less likely to mention their tax rates elsewhere in their disclosures, consistent with the choice of dollar format reflecting a firm's overall tax disclosure strategy. Analysts' tax expense forecasts are less accurate for dollar format firms, suggesting higher processing costs associated with tax-related disclosures for these firms. JEL Classifications: H20; G30; M40.